The impact of moral leadership on physical education teachers’ innovation behavior: The role of identification with leader and psychological safety - Chen, Jineng; Zheng, Wei; Jiang, Binbin (Frontiers in Psychology, 2022)
Considering that moral leadership can promote employees' innovation behavior through psychological factors, this study defines types of innovation behaviors, explores the impact of moral leadership on employees' innovation behavior from the perspective of identifying with leaders and psychological safety, and provides insights for schools to strengthen physical education (PE) teachers’ innovation behaviors. To this end, 327 questionnaires were distributed to PE teachers in Chinese provinces, and SPSS software was used to carry out an empirical analysis. The following conclusions were reached: first, moral leadership has a significantly positive effect on PE teachers’ psychological safety and internal and external innovation behaviors. Secondly, moral leadership affects employees' innovation behaviors through psychological safety, which has a partial mediating role between moral leadership and internal and external innovation behaviors; Thirdly, by comparing the two influence mechanisms of innovation behavior, we find that moral leadership stimulates employees to produce more external innovation behavior through psychological safety; Finally, a strong leadership identity positively regulates the relationship between moral leadership and innovation behavior.